2011
DOI: 10.1111/j.1468-2338.2011.00620.x
|View full text |Cite
|
Sign up to set email alerts
|

Labour standards and capacity in global subcontracting chains: evidence from a construction MNC

Abstract: This paper investigates how fundamental labour rights specified in International Framework Agreements are implemented and monitored in subcontracting chains. It shows how labour's capacity for workplace-based monitoring is influenced by factors such as ownership structures, the societal context, and, most importantly, the institutions and dynamics of local labour control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 23 publications
1
42
0
Order By: Relevance
“…Multiple sources of information, including earlier studies of IFAs (e.g., Hammer ; Davies et al. ; Papadakis ; Niforou ), also allowed data analysis triangulation (Jick ). Moreover, we received valuable feedback on the results of our case study research from representatives of management and unions in workshops organized in the four aforementioned countries.…”
Section: Ifas As An Instrument For Dealing With Risk and Uncertainty mentioning
confidence: 99%
“…Multiple sources of information, including earlier studies of IFAs (e.g., Hammer ; Davies et al. ; Papadakis ; Niforou ), also allowed data analysis triangulation (Jick ). Moreover, we received valuable feedback on the results of our case study research from representatives of management and unions in workshops organized in the four aforementioned countries.…”
Section: Ifas As An Instrument For Dealing With Risk and Uncertainty mentioning
confidence: 99%
“…It is also varied in terms of its focus on different facets of labour transnationalism, such as why GFAs do not result in meaningful gains at the local level, or the roles of supranational institutions such as European Works Councils. Examples can be seen in the works of Barrientos and Smith (2007), Davies et al (2011), Riisgaard and Hammer (2011) and Williams et al (2013). The units of analysis in this strand are also diverse, including movements, campaigns, bilateral alliances, multilateral alliances, global union federations, global value chains and, of course, GFAs.…”
Section: Introductionmentioning
confidence: 99%
“…It has been argued that GUFs, as sectoral federations, are positioned in very different ways with regard to strategy and the implementation of action across production networks and this is also thought to shape the politics of inter-union relations (Cumbers et al, 2008). The need for GUFs to develop varied, carefully designed and contextappropriate strategies in order to exercise power and influence over employers and states has also been noted (Brookes, 2013: 194), while studies of specific campaigns and initiatives (Davies et al, 2011;McCallum, 2013;Niforou, 2012) have shown the significance of local or regional context in determining the success or failure of avowedly 'global' initiatives -whether it be the established organizational forms and repertoires of local or national unions or the configuration of politics, governance or employment relations in particular settings. This would appear to be especially relevant to the effect of global campaigns and regulatory initiatives on workplaces situated in the Global South where unions are often weak, fragmented and have limited institutional and associational power (Brookes, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…With regard to global agreement making, for instance, some studies have pointed to the positive effect of IFAs/GFAs under certain circumstances, but many others emphasize the limited translation of formal agreement making at global/corporate level into action by managers, workers and unions at industry or enterprise level (Davies et al, 2011;Niforou, 2012). This is in part a problem of the failure to build implementation measures into agreements that are ultimately far removed from local contexts.…”
Section: Agents Of Change or Marginal Actors?mentioning
confidence: 99%